EFEITO DO USO DE PROBIÓTICOS NA SINTOMATOLOGIA GASTROINTESTINAL DA DOENÇA CELÍACA: UMA REVISÃO NARRATIVA (REMUNOM, 2025)
Celiac disease (CD) is an autoimmune enteropathy triggered by gluten ingestion, leading to chronic inflammation of the small intestine and gastrointestinal symptoms such as diarrhea, abdominal pain, and bloating. The only known effective treatment is strict adherence to a gluten-free diet. However, some patients continue to experience gastrointestinal symptoms even with dietary restriction. In this context, probiotics have been investigated as a complementary strategy for modulating the gut microbiota and alleviating persistent symptoms in individuals with CD. This narrative review aims to analyze the available scientific evidence regarding the relationship between probiotic use and gastrointestinal symptoms in celiac patients. A comprehensive search was conducted in scientific databases to identify studies that evaluated the impact of probiotics on symptom relief and intestinal health in this population. The literature suggests that probiotics may contribute to the balance of gut microbiota, strengthening of the intestinal barrier, and reduction of pro-inflammatory responses. Some studies reported improvements in symptoms such as bloating and changes in bowel habits. However, the results are inconsistent, with great variability in study design, probiotic strains used, treatment duration, and patient profiles. This heterogeneity limits the ability to draw definitive conclusions about efficacy. Thus, the analyzed data suggest that the use of probiotics may represent an effective complementary nutritional approach in the management of celiac disease, especially in patients who continue to experience symptoms despite a gluten-free diet. However, their use should be guided by qualified healthcare professionals, considering individual needs, with the goal of modulating inflammatory responses, restoring microbiota balance, and improving quality of life.  Keywords:  Celiac disease. Probiotics. Gluten. Gut microbiota. Gastrointestinal symptoms